2020
DOI: 10.1155/2020/3462342
|View full text |Cite
|
Sign up to set email alerts
|

Property Improvement of Cement Emulsified Asphalt Paste Modified by Graphene Oxide

Abstract: Cement emulsified asphalt paste (CEAP) is widely used as a construction and building material by combining the advantages of cement rigidity and asphalt flexibility. However, the properties of CEAP can be evidently reduced due to the addition of emulsified asphalt. In this work, graphene oxide (GO) was prepared by the Hummers method and was innovatively used to improve the workability and strength of CEAP. The viscosity of CEAP was tested by Brookfield viscometer. In addition, the effects of GO on the setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Graphene oxide (GO) is a single atomic layer formed by the oxidation of graphite, with a unique quasi-dimensional layered structure, excellent oxygen barrier, and good intersolubility with organic solvents, gaining attention as a new modifier for asphalt [ 6 , 7 , 8 ]. Research in recent years has found that graphene oxide as a modifier can improve the elastic response and road performance of the asphalt matrix, forming a more stable molecular structure [ 9 , 10 ]. In addition, the cost of nanomaterials has shown a decreasing trend, and with improvements in manufacturing technology, their costs are likely to decrease further [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide (GO) is a single atomic layer formed by the oxidation of graphite, with a unique quasi-dimensional layered structure, excellent oxygen barrier, and good intersolubility with organic solvents, gaining attention as a new modifier for asphalt [ 6 , 7 , 8 ]. Research in recent years has found that graphene oxide as a modifier can improve the elastic response and road performance of the asphalt matrix, forming a more stable molecular structure [ 9 , 10 ]. In addition, the cost of nanomaterials has shown a decreasing trend, and with improvements in manufacturing technology, their costs are likely to decrease further [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This work is the first time that, to the best of our knowledge, small quantities of multilayer GO were used to produce high-performing liquid bituminous membranes with a waterproofing function. A low GO concentration was selected according to the literature [ 43 , 44 ] in order to have a low impact on production cost and, thus, to be competitive in the target market. Therefore, this study aimed to analyze the effect of the low graphene oxide concentration on the mechanical resistance of the produced membrane, how the GO doping impacts the barrier properties, and its properties as an anti-aging agent.…”
Section: Introductionmentioning
confidence: 99%
“…To compensate for the disadvantages of the above conventional materials in terms of construction technology, economy, environmental protection, and road performance, the use of a new bitumen/cement composite stabilized mixture with early-strength, self-compacting, and room-temperature construction characteristics (CEBM) for road maintenance is proposed, which may have adequate applications for repairing potholes in the asphalt pavement quickly and conveniently. Using sulphoaluminate fast-hardening cement and emulsified bitumen as the composite binders for CEBM can not only achieve the rigidity [ 34 ] enabled by cement but also meet the load-bearing capacity and improve high-temperature anti-rutting. The bitumen also has the flexibility [ 35 ] to meet the requirements of low-temperature cracking resistance and medium-temperature fatigue resistance [ 36 ].…”
Section: Introductionmentioning
confidence: 99%